Wound Healing Recent Advances and Future Opportunities - Colette Maurício, Ana; Alvites, Rui; Gönül, Müzeyyen (IntechOpen, 2023)
Skin wounds are common occurrences that result from the breakdown of anatomical continuity and integrity of the epidermis, with consequent functional changes. Wound healing is a complex phenomenon through which there is healing of the skin. The wound healing process begins immediately after the wound occurs and can be a lengthy and complex process depending on the severity of the wound and the normal or abnormal healing progress. Wound healing progress through three distinct phases of inflammation, proliferation, and remodeling in a methodical and complex sequence that involves cellular, molecular, and humoral mechanisms of action. Any change in this sequence of events can lead to abnormal wound healing. Due to the health and psychological consequences of wounds that are difficult to heal there has been a continuous effort to develop new therapies that promote wound healing more quickly and effectively and that restore the skin's barrier function. Nevertheless, this situation remains a medical challenge. This book presents some therapeutic advances based on new and innovative therapeutic options, medical devices, and biomaterials to promote wound healing. It is a theoretical and practical reference for future research on chronic wound healing.